Can avoidance in Enchytraeus albidus be used as a screening parameter for pesticides testing? - Novais, Sara C.
Enchytraeids are important inhabitants of a wide variety of soil types and suitable test organisms for environmental risk assessment through the determination of effects on survival and reproduction. In this study, the effect of pesticides with different modes of action is assessed in the standard test species Enchytraeus albidus. Main goals were: (a) to test the toxicity of a range of pesticides to E. albidus in a natural soil (LUFA 2.2), (b) to assess whether avoidance gave a prediction of effects on the survival and reproduction, and (c) to investigate if the organisms' response to different toxics can be grouped into the respective chemical classes. Pesticides selected were the: (1) herbicides: phenmedipham and atrazine; (2) fungicides: carbendazim and pentachlorophenol: and (3) insecticides: dimethoate and lindane. All tested pesticides caused effects in the survival and reproduction of E. albidus and the compounds that showed a higher toxicity were carbendazim, dimethoate and atrazine. The effect concentrations were not chemical class dependent. In general, survival and reproduction showed similar response patterns. Avoidance behaviour showed trends of response similar to these other measured endpoints, but was less sensitive and more variable (data from a previous study). It was not possible to establish a clear correlation between survival, reproduction and avoidance endpoints. From an ecological point of view, avoidance tests are relevant but due to lower sensitivity and higher variability it is recommended that the enchytraeid avoidance test should not be used for risk assessment purposes. (C) 2010 Elsevier Ltd. All rights reserved.